Firm climate change risk and financial flexibility: Drivers of ESG performance and firm value - Mirza Muhammad Naseer; Muhammad Asif Khan; Tanveer Bagh; Yongsheng Guo; Xiaoxian Zhu (Borsa İstanbul Review, 2024)
This study investigates how a firm's climate change risk (FCCR) and financial flexibility (FIFL) affect its value and environmental, social, and governance (ESG) performance. We use data from publicly listed US firms for 2012-2021. We employed four estimation methods: bootstrap quantile regression, feasible generalised least squares, a generalised method of moments, and fixed effects with Driscoll-Kraay standard errors. Our main findings indicate that climate change risk has a negative effect on firm value and a positive effect on ESG performance and that financial flexibility moderates these effects by reducing risk and enhancing value. These results are robust against alternative measures and estimation techniques. Our study provides novel insights into the influence of climate risk and financial flexibility on firm value and ESG performance. We also discuss the implications of our results for academics, practitioners, and policymakers.
Keywords: Q54; Q56; G32; M14; 330; Firm climate risk; Financial flexibility; Firm value; Tobin's Q; ESG